Reconstructed recovery healing-generative architecture through an accessible and inclusive Philippine Orthopedic Center - Taruc, Jacob Brendan S.; Ong, Simoun T. (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
The sudden rise in the need for healthcare during the COVID-19 pandemic revealed
the state of the world’s medical systems and their capacity for patient care. Presently,
there is a huge burden on the existing healthcare systems which raises problems
related to the capability of facilities to cater a high volume of patients with specific
health issues and requires distinct care. During this period, architects were put into
the spotlight for being at the forefront of providing solutions for medical issues faced
within the hospital.
The Philippines was among the countries that struggled and faced crucial challenges
in healthcare. In an effort to address these issues, the government established goals
for the improvement of healthcare facilities in the country. One of the hospitals that
the government has offered funding is the 60-year-old Philippine Orthopedic Center.
This paper aims to address the current state of the Philippine Orthopedic Center. The
hospital faces significant issues with its facilities in terms of accommodating
physically-limited patients suffering from bone and muscle traumas, illnesses and
injuries.
The paper gathers various strategies proven to be effective in hospital design to aid
the user-behavior of the hospital’s primary stakeholders in establishing a framework
for design. This study aims to corroborate key information regarding the universal
requirements for hospitals as well as the local customs and needs of a Philippine
hospital.
The thesis ultimately provides a design applying the values of sustainability, on and
accessibility for the provision of healthcare facilities through the Philippine
Orthopedic Hospital.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Health facilities -- Philippines; Philippine Orthopedic Hospital; Hospital architecture -- Philippines